Social capital shapes mahasantri’s social care character at Ma'had Al-Jami'ah UIN Siber Syekh Nurjati Cirebon - Ummah, Ima Saadatul; Masrukhi, Masrukhi; Atmaja, Hamdan Tri (Universitas Negeri Semarang, 2024)
The social capital of Ma'had Al-Jami'ah UIN Siber Syekh Nurjati Cirebon serves as a critical factor in shaping the social care character of its mahasantri. This article aims to analyze the social capital of the Ma'had and examine the formation of social care character among the mahasantri. A qualitative methodology with a case study approach was employed. The data sources included informants, document studies, and events. Data collection techniques involved observation, interviews, and documentation. Data validity was ensured through methodological triangulation. The data analysis techniques encompassed data collection, data reduction, data display, and conclusion drawing. The research was conducted at Ma'had AlJami'ah UIN Siber Syekh Nurjati Cirebon. The findings indicate that social capital at this Ma'had is evidenced by interactions that foster kinship, togetherness, and networks among mahasantri, tutors, administrators, and the director. The social care character among the mahasantri is cultivated through communal activities such as cleaning, Marhabanan and Muhadoroh ceremonies, sharing food, caring for ill comrades, and lending money to those in need. The conclusion of this study is that the social capital at the Ma'had effectively promotes the development of social care character among mahasantri through various activities within the Ma'had environment.